Teaching grammar is not my main responsibility": Exploring EFL teachers' beliefs about grammar teaching - Tuğba Elif Toprak (Informascope, 2019)
This mixed-methods study investigated a hundred university EFL teachers' beliefs about several issues in grammar teaching. Teachers' beliefs about these issues such as the explicit and implicit teaching of grammar, its integration with other language skills, and the role of a teacher in grammar teaching were elicited by means of a questionnaire. Furthermore, semi-structured interviews were conducted with ten volunteer teachers to obtain more in-depth information about teachers' reported beliefs. These results were analyzed by using the descriptive statistics and in-vivo coding. The findings of the study demonstrated that most teachers believed in the centrality of grammar instruction to helping language learners attain a substantial proficiency in English. Moreover, it was found that most teachers favored an inductive, integrative and communicative approach to grammar teaching. Although teachers' reported beliefs were, overall, in harmony with the literature on grammar teaching, there were no hints suggesting that teachers were aware of grammar theories or their beliefs were based on SLA/grammar literature. The findings indicated that the distinction between pedagogical dichotomies proposed in the literature seemed to blur in the practice since teachers frequently referred to personal and contextual features as the main factors shaping their beliefs and practices.